Wanted : toddler's personal assistant : how nannying for the 1% taught me about the myths of equality, motherhood, and upward mobility in America - Kiser, Stephanie (Sourcebooks, 2024)
"After a dysfunctional childhood as one of four kids born to teenage parents and raised "white trash" in poor Rhode Island, Stephanie Kiser finds herself a 22-year-old first-generation college grad drowning in student loan debt. To stay afloat, she surrenders her career-track PR job for a position as nanny to New York City's toddler elite. The span of seven years takes Stephanie on a journey from working alongside a stay-at-home mom in her ten-million dollar Park Ave apartment, to a "no discipline" family, to the Kushner's, world-class doctors and finally, to a position with a young couple, both high-powered lawyers, with three small kids. Interwoven with Stephanie's time in the glamourous world of the 1% (in the unglamourous role of domestic help) is the narrative of her own upbringing, the contrasts illuminating both the effects of privilege and the grit of self-sufficiency"--